From Quality to Loyalty: The Brand image Effect in Viva Cosmetics Journey - Prasetyawati, Novela; Novitasari, Risma; Khoirunnisa, Miftah; Nurnafiah, Annisa (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
The beauty industry is becoming increasingly competitive; however, Viva Cosmetics remains a prominent brand with a positive image among consumers. This study examines the influence of product quality on customer loyalty, with brand image as a mediating variable, among Viva Cosmetics consumers in Surakarta. Using a quantitative approach, the study involved 99 respondents selected through purposive sampling. Data were analyzed with variance-based Structural Equation Modeling (SEM) using SmartPLS 4. The results reveal that product quality has a positive and significant impact on both customer loyalty and brand image. However, brand image does not significantly affect customer loyalty, indicating it does not mediate the relationship between product quality and customer loyalty. Thus, customer loyalty is more directly driven by product quality. The study suggests that Viva Cosmetics should explore alternative mediating variables to enhance customer loyalty